Reforma a vapor do etanol sobre catalisadores de Co - Ni/MgAl2O4: propriedades estruturais e catalíticas em função da temperatura de reação - Braga, Adriano Henrique (Universidade Federal de São Carlos, 2016)
This thesis studied the effect of Co addition to Ni-based catalysts, focused on electronic and structural modification, as well as how these changes interfere on the catalytic properties, like reaction pathway and carbon accumulation towards steam reforming of ethanol (SRE), addressed by in-situ and ex-situ methods. Two series of bimetallic CoNi catalysts with different total metal loading of 8 and 15 wt% were prepared by impregnation of MgAl2O4 support with aqueous solution of Co and Ni salts. Different techniques were used for physicochemical characterization of the samples based on X-ray methodos and electron microscopy. Catalytic tests of ethanol steam reforming were carried out in a wide temperature region from 300 to 650°C. The dependence of ethanol conversion and product distribution as a function of metal loading and temperature reaction were evaluated. It was shown that the undesirable methane formation over Ni catalyst is hindered by Co addition. X-ray based characterization of bimetallic CoNi system suggested that: (i) a spinel-like phase NiCo2O4 is formed, which once reduced originates an alloy and (ii) the lattice parameters and bond distance are changed compared to those of parent metals. X-ray spectroscopy showed a presence of Ni in oxidation state of +3, and that this high valence specie is enhanced when the particle size is decreased by the decrease of metal loading. Results of in-situ characterization showed the dynamics of the catalysts towards ethanol reforming. With Co addition, the level of surface oxide driven by reaction stream increases sensibly, modifying the catalytic properties. The alloy has different redox behavior with respect to the monometallic catalysts, being easily oxidized than monometallic Ni, and on the other hand it controls the oxidation better than monometallic Co. Thus, the alloy is an important factor in the behavior of the catalysts with respect to carbon accumulation and the selectivity to methane during SRE, both diminished compared to Ni. Regarding metal particle size of bimetallic catalysts, the large particles (9,9 nm) are more insensible to reaction atmosphere, whereas at smaller nanoparticles (4,2 nm), the surface composition is tuned by the redox potential of reactants and products. Consequently, a distinct reaction pathway is caused by the change in structure of the bimetallic catalyst, improving the stability towards SRE. These data point to important features that influence the performance of classical catalysts for ethanol reforming reaction, thus playing a key role for the development of novel materials.
Steam reforming of ethanol on Co - Ni/MgAl2O4 catalysts: structural and catalytic properties as function of reaction temperature
Keywords: Etanol; Bimetálicos; In-situ; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA